Ross Ice Shelf Cavity Ocean Data ... - Stevens, Craig; Brewer, Mike; Grant, Brett (SEANOE, 2017)
Here we provide data from the Ross Ice Shelf ocean cavity. Location - The HWD2 Camp was established in October of 2017 at 80o 39.497’S, 174o 27.678’E where the ice is moving seaward at around ~600 m a-1 and is sourced from the Transantarctic Mountains. Profiling Instruments - Profiling was primarily conducted with an RBR Concerto CTD (conductivity-temperature depth) profiling instrument, and this was cross-calibrated against irregular profiles with an RBR Duet (pressure and temperature only), a SBE37 MicroCat CTD as well as moored SBE37 MicroCat CTDs. The RBR unit is small and has suitable sensor capability (temperature and conductivity accuracies of ±0.002°C and ±0.003 mS cm-1). Its conductivity cell design is not prone to fouling by ice crystals, making it ideal for work in the sometimes crystal-laden borehole conditions. We were inconsistent in how we mounted the CTD on its protective frame and this appeared to make small difference in the conductivity signal (resulting in an ~0.03 psu variation). This ...